2004
DOI: 10.1095/biolreprod.104.028605
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Sperm with Purified Native Chicken ZP1 and ZPC Proteins1

Abstract: The avian perivitelline membrane (PVM) is the site of initial contact between sperm and egg. It consists of only two major components, which are both homologues of the mammalian zona pellucida (ZP) proteins, and belong to the ZP1 and ZPC families, respectively. We have established a method to isolate large quantities of both native avian ZP proteins and have used these preparations to investigate their sperm-binding capacities. Chicken ZPC forms multimeric structures of defined size and binds to an approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 32 publications
2
25
1
3
Order By: Relevance
“…It is quite interesting that sperm binding to the PL in chicken appears to be mediated by both ZP1 and ZP3 (Bausek et al 2004). Although both ZP3 and ZP1 bind to the acrosomal region of rooster sperm, only ZP1 possesses the activity for AR induction (Okumura et al 2004 and in this study).…”
Section: Acrosome Reaction In Japanese Quailsupporting
confidence: 46%
See 1 more Smart Citation
“…It is quite interesting that sperm binding to the PL in chicken appears to be mediated by both ZP1 and ZP3 (Bausek et al 2004). Although both ZP3 and ZP1 bind to the acrosomal region of rooster sperm, only ZP1 possesses the activity for AR induction (Okumura et al 2004 and in this study).…”
Section: Acrosome Reaction In Japanese Quailsupporting
confidence: 46%
“…Although the reason for this discrepancy between chicken and quail is not investigated in this study, these authors used a gel filtration technique with buffer containing 6 mol/l urea, whereas we employed SDS-PAGE under non-reducing conditions for the purpose of ZP1 purification. On the other hand, Bausek et al (2004) have demonstrated that both ZP3 purified from a culture supernatant of granulosa cells and ZP1 obtained from the serum of laying hens are bound to the acrosomal region of rooster sperm by means of immunofluorescent microscopy. In addition, they also showed that both ZP3 and ZP1 interact with a 180 kDa protein present in the lysate of rooster sperm.…”
Section: Acrosome Reaction In Japanese Quailmentioning
confidence: 99%
“…At the state of the F1 follicle, the PL is composed of the IPVL in construction (Elis et al 2008), very closely surrounded (tide junctions) by granulosa cells. At the ovulation state, the PL is composed of IPVL mainly comprising ZP proteins (Waclawek et al 1998, Takeuchi et al 2001, Bausek et al 2004, Okumura et al 2004. At the oviposition state, a mean of 24 h after ovulation and possible in vivo fertilization, the PL is composed of two layers, the IPVL and the OPVL.…”
Section: Discussionmentioning
confidence: 99%
“…The IPVL can be considered to a certain extent as analogous to the mammalian zona pellucida (ZP; Waclawek et al 1998). It consists of ZP glycoproteins that are homologous to the mammalian ZP proteins known to have a key role in sperm binding to the ZP and in the induction of acrosomal exocytosis (Waclawek et al 1998, Takeuchi et al 2001, Bausek et al 2004, Okumura et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…There are three possible explanations of this inhibitory effect; 1, the sperm-egg binding is inhibited by the antiserum because the antiserum covered the ZP3, a binding site for the spermatozoa; 2, the acrosome reaction of the sperm was blocked by the antiserum; 3, the protease responsible for the digestion of pvm is inhibited by the antiserum. Although we did not perform further experiments, Bausek et al (2004), who tested the binding of purified ZP1 or ZP3 to the sperm demonstrated that both ZP proteins specifically bind to the tip of the sperm head. However, only ZP3 binding occurred through the interaction with 180 kDa sperm protein in the chicken.…”
Section: Sperm-egg Bindingmentioning
confidence: 95%